Reserves accumulation in African countries: Sources, motivations, and effects - Adam Elhiraika; Léonce Ndikumana (University of Massachusetts, Department of Economics, 2007)
African countries have accumulated substantial foreign currency reserves in recent years, mostly from higher commodity exports as well as aid flows. In the context of macroeconomic stabilization, which remains at the forefront of national economic policymaking and aid conditionality, African countries are induced to hold reserves to allow monetary authorities to intervene in markets to control the exchange rate and inflation. Adequate reserves also allow the country to borrow from abroad and to hedge against instability and uncertainty of external capital flows. However, reserve accumulation can have high economic and social costs, including a high opportunity cost emanating from low returns on reserve assets, losses due to reserve currency depreciation, and forgone gains from investment and social expenditures that could be financed by these reserves. Therefore, African countries need to have a better understanding of the determinants and economic costs of reserve accumulation and to design optimal reserve management strategies to minimize these costs and maximize the gains from resource inflows. This study uses panel data from 21 African countries to examine the sources, motivation and economic implications of reserve accumulation with a focus on the impact on the exchange rate, inflation, and public and private investment. While the level of reserves remains adequate on average, some countries have accumulated excessive reserves especially in recent years.
Keywords: E22; E51; F31; F41; 330; external reserves; exchange rate appreciation; sub-Saharan Africa; private and public investment; macroeconomic stabilization; Währungsreserven; Kosten-Nutzen-Analyse; Währungspolitik; Soziale Kosten; Makroökonomischer Einfluss; Investition; Schätzung; Afrika südlich der Sahara